Pengaruh Pembelajaran Kewirausahaan, Entrepreneurial Traits, dan Literasi Digital terhadap Rintisan Bisnis Mahasiswa - Dyah Arsakiyana; Raya Sulistyowati (Jurnal Ecogen, 2022)
The increasingly rapid economic growth and the progress of the modern era of entrepreneurship are considered to be able to support the potential to increase economic growth. Growing interest in entrepreneurship is now getting more and more attention, especially for university students who are required to be economically independent. One of the ways to improve the spirit of entrepreneurship is by providing entrepreneurship courses. With the knowledge and attitudes already possessed by the students of the Faculty of Economics and Business, State University of Surabaya, they have implemented it by establishing a business startup. This study intends to analyze and determine the effect of learning entrepreneurship, entrepreneurial traits, and digital literacy on business startups for students of the Faculty of Economics and Business, State University of Surabaya. This quantitative study used 112 student respondents as the research sample. Data was collected using a questionnaire and processed using a Structural Equation Modeling (SEM) model using Partial Least Squares (PLS) which was processed using SmartPLS 3.0 software. This study concludes that learning entrepreneurship, entrepreneurial traits, and digital literacy can significantly influence student business startups.